Effect of biomass immobilization and reduced graphene oxide on the microbial community changes and nitrogen removal at low temperatures - Anna Banach-Wiśniewska (Nature Portfolio, 2021)
Abstract The slow growth rate and high optimal temperatures for the anaerobic ammonium oxidation (anammox) bacteria are significant limitations of the anammox processes application in the treatment of mainstream of wastewater entering wastewater treatment plant (WWTP). In this study, we investigate the nitrogen removal and microbial community changes in sodium alginate (SA) and sodium alginate–reduced graphene oxide (SA-RGO) carriers, depending on the process temperature, with a particular emphasis on the temperature close to the mainstream of wastewater entering the WWTP. The RGO addition to the SA matrix causes suppression of the beads swelling, which intern modifies the mechanical properties of the gel beads. The effect of the temperature drop on the nitrogen removal rate was reduced for biomass entrapped in SA and SA-RGO gel beads in comparison to non-immobilized biomass, this suggests a ‘‘protective” effect caused by immobilization. However, analyses performed using next-generation sequencing (NGS) and qPCR revealed that the microbial community composition and relative gene abundance changed significantly, after the implementation of the new process conditions. The microbial community inside the gel beads was completely remodelled, in comparison with inoculum, and denitrification contributed to the nitrogen transformation inside the beads.